2021
DOI: 10.1515/opag-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Influences of spacing on yield and root size of carrot (Daucus carotaL.) under ridge-furrow production

Abstract: Although there is adequate information on the influence of plant population on root yield and size of carrot on flat and raised bed for rain fed production system, information on ridge-furrow bed preparation method is limited for irrigation production system. Therefore, in this study, field experiments were conducted for 2 years to determine the appropriate spacing of carrot on ridge-furrow carrot production practice under irrigation. Root yield increased significantly as the population increased. On the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…High plant density (90,000 plants per ha) reduced the number of nodal roots, lateral root density, and average lateral root length in field-grown maize [38]. Tegen et al [39] reported that the highest root diameter of carrots occurred at the widest interrow spacing of 30 cm. Lower plant density has also been reported to increase average root weight and dry matter content for radishes [40].…”
Section: Root Number Root Fresh Weight and Root Dry Weightmentioning
confidence: 99%
“…High plant density (90,000 plants per ha) reduced the number of nodal roots, lateral root density, and average lateral root length in field-grown maize [38]. Tegen et al [39] reported that the highest root diameter of carrots occurred at the widest interrow spacing of 30 cm. Lower plant density has also been reported to increase average root weight and dry matter content for radishes [40].…”
Section: Root Number Root Fresh Weight and Root Dry Weightmentioning
confidence: 99%
“…Carrot yields per unit area in most developing countries remain below the recommended world average [53]. In Nigeria, cool-season vegetables are mainly grown in highaltitude regions of Northern districts where a mild subtropical climate prevails [6].…”
Section: Introductionmentioning
confidence: 99%